El adulto mayor y la patología otorrinolaringológica - Cabello E., Pablo; Bahamonde S., Héctor (Revista Hospital Clínico Universidad de Chile, 2008)
During the past years Chile has suffered a change on its demographics. Nowadays is a country with an aged country profile. This is reflected in the raise of elderly population attending to otolaryngologist attention. This population develops pathologies tightly related to aging process that become a frequent chief complaint. This review looks into common otolaryngological complaints within elderly population such as voice disorders, balance disorders, presbycusis, tinnitus, dysphagia, nasal disorders and head and neck cancer.